A escola e a covid-19: os impasses do trabalho docente na Escola SESI São Luis – Anexo - ARAÚJO FILHO, Demerval Santana de (2024)
This dissertation's main goal is to analyze and discuss the changes caused by the Covid-19 pandemic in teaching work in São Luís city context at the SESI São Luís Annex school, in the year 2021 with the aim of contributing qualitatively to the discussions relating to teaching work and the social mediations in the school environment. In specific terms, understand which discourses constructed and reproduced in the school space motivate (or not to), students during the year 2021, what are the meanings of the work carried out by teachers, analyze the consequences of students' physical deprivation in the classroom and understand the resignifications that these professionals had to go through to continue carrying out their activities. It discusses the teaching work carried out at the SESI São Luis Annex school and the strategies adopted by teachers to teach their classes. Furthermore, it discusses the effects of the Covid-19 pandemic in the face-to-face classroom. Adopting a qualitative and quantitative approach, it promotes a characterization of the interviewees (teachers and students), with the aim of analyzing training aspects in order to understand the actions undertaken in the classroom. The study proposed here, in addition to semi-structured interviews, used questionnaires and on-site observations with the aim of verifying the discourses that permeated the resignifications of teaching work and those mediated in 2021 exclusively through digital platforms. Taking as a reference official documents such as: CNE/CP Resolution no 2, of August 5, 2021, CNE/CP Resolution no 2, of December 10, 2020, CNE/CP Opinion no 5/2020 and Oswaldo Cruz Foundation (2022). These documents stated the different stages in the evolution of Covid-19 in Brazil and the different actions adopted to contain the virus. It was possible to notice that there was a deepening of the precariousness of teaching work, since there was a lack of digital resources to deal with the new reality. Furthermore, the growing massification of virtual platforms can be noted as the main means of constructing school knowledge. Furthermore, a significant increase in school conflicts was noticed, possibly resulting from the period of social isolation during the pandemic period, especially in 2021.